2015
DOI: 10.1039/c5cp01846c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of the chromium-doped iron sulfide Fe1−xCrxS single crystalline nanoplates with a NiAs crystal structure

Abstract: Single crystalline iron sulfide nanoparticles doped with chromium Fe1-xCrxS (0 ≤x≤ 0.15) have been successfully prepared by a thermal decomposition method. The particles are self-organized into the single crystalline plates with the accurate hexagonal shape and dimensions up to 1 μ in plane and about 30-40 nm in thickness. The samples have the NiAs-type crystal structure (P63/mmc) at all Cr concentrations up to x = 0.15. Fe(57)-Mössbauer spectroscopy data reveal four nonequivalent iron sites in these nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Magnetic effects in valleriites can be modified via a number of factors, for example, compositions of sulfide (Fe, Cu)­S 2 and hydroxide (Mg, Al, Fe)­(OH) 2+ x layers and their electrical charges, a number of the atomic layers, external electric and magnetic fields, and so on. Moreover, the composition of valleriite-like materials can be changed in a very wide range as there exist minerals in which magnesium is replaced by iron in hydroxide layers (“ferrovalleriite”), , or iron is substituted by chromium in sulfide sheets, , or mackinawite-type iron sulfide layers with no copper in tochilinite or ferrotochilinite. ,, In addition to the magnetic properties, superconductivity has been reported in such iron chalcogenide layers . Consequently, valleriite emerges as a platform for numerous two-dimensional composite materials, exhibiting very special and tunable properties for various applications.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic effects in valleriites can be modified via a number of factors, for example, compositions of sulfide (Fe, Cu)­S 2 and hydroxide (Mg, Al, Fe)­(OH) 2+ x layers and their electrical charges, a number of the atomic layers, external electric and magnetic fields, and so on. Moreover, the composition of valleriite-like materials can be changed in a very wide range as there exist minerals in which magnesium is replaced by iron in hydroxide layers (“ferrovalleriite”), , or iron is substituted by chromium in sulfide sheets, , or mackinawite-type iron sulfide layers with no copper in tochilinite or ferrotochilinite. ,, In addition to the magnetic properties, superconductivity has been reported in such iron chalcogenide layers . Consequently, valleriite emerges as a platform for numerous two-dimensional composite materials, exhibiting very special and tunable properties for various applications.…”
Section: Resultsmentioning
confidence: 99%
“…have reported the preparation of Mn 2+ doped ZnS nanorods using green phosphine‐free colloidal chemistry and observed tunable blue and orange emission [14] . The synthesis of Cr doped FeS nanoparticles using thermal decomposition method and investigation of their magnetic properties have been reported by Starchikov et al [15] …”
Section: Introductionmentioning
confidence: 98%
“…[13] Deng et al have reported the preparation of Mn 2 + doped ZnS nanorods using green phosphine-free colloidal chemistry and observed tunable blue and orange emission. [14] The synthesis of Cr doped FeS nanoparticles using thermal decomposition method and investigation of their magnetic properties have been reported by Starchikov et al [15] Nanomaterials which possess enzyme-like activity are known as nanozymes (artificial enzymes) and they can be useful in biosensing, nanomedicine, environmental treatment and antibacterial activity. [16] Nanozymes can be easily synthesized, cheaper, stable, and durable as compared to natural enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al [23] have deposited the Co-doped FeS2 thin films for water photolysis utilizing sunlight by Solvothermal method with enhanced photo response. Starchikov et al [24] reported the Cr doped Fe1-xCrxS single crystalline nanoplates for energy storage devices by a facile thermal decomposition technique. The fabricated Cr doped Fe1-xCrxS composite showed the enhanced magnetic properties.…”
Section: Introductionmentioning
confidence: 99%